Systematic Literature Review: Pengaruh Metode Latihan Sircuit Training dan Interval Training Terhadap Kebugaran Peserta Didik - I Ketut Wisata; I Ketut Sudiana; I Ketut Semarayasa (Jurnal Porkes, 2026)
A common problem faced by physical education (PJOK) teachers is the low endurance or fitness levels of their students. Some students easily become fatigued even after only light physical activity, hindering the learning process as teachers have difficulty moving on to the next topic or activity. This study aims to analyze, synthesize, and compare the effectiveness of circuit training and interval training methods on student fitness. This systematic review included eight selected studies that met the inclusion criteria based on the PICOS framework. A literature search was conducted in scientific databases using the keywords "circuit training," "interval training," and "fitness." The article selection process followed the PRISMA 2020 guidelines, while the literature review was structured using the SALSA framework. The research subjects came from various countries and involved elementary, junior high, and high school students. The synthesis results showed that both methods improve physical fitness, but interval training tends to be more effective in improving cardiovascular endurance, while circuit training is superior in developing overall muscle strength and endurance. Pedagogical implications in PJOK learning emphasize that teachers need to adjust the selection of training methods to the learning objectives, student characteristics, and class conditions, for example using interval training to increase stamina and circuit training for integrated physical strengthening, so that PJOK learning becomes more systematic, safe, varied, and oriented towards optimally improving student fitness.